Distillers dried grain with solubles effectively replaces soybean meal as a protein source in Boer goat diets - Hutchins, Rachel E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Including distillers dried grain (DDGS) as a protein source to replace soybean meal (SBM) in Boer goat diets is a viable option for reducing feed costs. With the per protein unit cost advantage of DDGS over SBM being $1.86, DDGS would clearly price into goat diets as a protein source (October 26, 2017 U.S. Grains Council Report). However, there is very limited research regarding DDGS inclusion in goat diets. The goal of this experiment was to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. For this experiment, forty-eight meat goat kids (approximately 70 d of age) with similar weights were used in a completely randomized design. Kids were housed with 3 kids per pen (4 pens per treatment) and allotted into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All diets were pelleted and contained roughage, so no supplemental forage was needed. This facilitates a more precise calculation of average daily feed intake (ADFI) and the gain to feed ratio (G:F). Diets were fed for 47 days after a 14 day step up period, with average daily gain (ADG), ADFI, and G:F calculated weekly. Data was analyzed using the GLIMMIX procedure of SAS with pen serving as the experimental unit. Once the feeding period ended, two goats per pen were slaughtered so we could collect carcass data. At the conclusion of this experiment, there were no statistical differences in ADG (P=0.032), ADFI (P=0.538), G:F (P=0.005), hot carcass weight (P=0.480), and carcass yield (P=0.878) when we replaced SBM with DDGS. However, there were distinct numerical differences in ADG, where goats fed 66% and 100% DDGS in place of SBM gained 0.02 kg/d more than those fed 0% DDGS. The lack of statistical differences in each treatment presents a strong case that producers can effectively use DDGS as a protein source in Boer goat diets to yield relatively similar performance and carcass characteristics as diets utilizing SBM. The results from this experiment imply that producers could utilize cost effective means of reducing feed costs and promote growth in US corn and meat goat production.
Keywords: Spring 2018